Except for the very first one you posted, these are all pretty much the same.
The very first one had f ( g(x) )
You had to take a function of a function.
The rest of these seem to be simple additions, subtractions, multiplications, or divisions.
Here just add f(x) to g(x) to get (f+g)(x)
let f(x)= 2x+8 and g(x)= x+4
(f+g)(x)
3 answers
oo duh. lol thank you!
Perhaps this might help
Say f(x) = x^2 and g(x)=x^3
then
f(x)g(x) = x^(2+3) = x^5
BUT
f(g(x)) = (x^3)^2 = x^6
Say f(x) = x^2 and g(x)=x^3
then
f(x)g(x) = x^(2+3) = x^5
BUT
f(g(x)) = (x^3)^2 = x^6